Pengaruh Kualitas Software, Akurasi Informasi, Ketepatan Waktu Informasi, dan Relevansi Informasi terhadap Kepuasan End-User Sistem Informasi Akuntansi: Studi Empiris pada Karyawan Perusahaan Retail Department Store Wilayah Jakarta - Leonardo, Amadeo; Sparta, Sparta (Ultimaccounting Jurnal Ilmu Akuntansi, 2015)
The objective of this research to test, examine and to provide empirical evidence to the influence of accounting software quality, accuracy of the information, timeliness of the information and relevance of the information toward the accounting information system enduser satisfaction. The research was conducted using a survey method to to provide the questionnaires to the employees in retail department store. Data used in this study was primary data, id est: questionnaires. The respondents in this study were 118. Data analysis techniques in this study using multiple linear regression. The results of this study were (1) accounting software quality had a significant influence toward the accounting information system end-user satisfaction; (2) accuracy of the information had no significant influence toward the accounting information system end-user satisfaction; (3) timeliness of the information had a significant influence toward the accounting information system end-user satisfaction; (4) relevance of the information had a significant influence toward the accounting information system end-user satisfaction; (5) accounting software quality, accuracy of the information, timeliness of the information and relevance of the information had significant influence toward the accounting information system end-user satisfaction simultaneously. Keywords: Accounting information system end-user satisfaction, Accounting software quality, Accuracy of the information, Timeliness of the information, Relevance of the information.